Who Will Advocate? The Impact of Decision 93/PUU-XX/2022 on Article 433 Civil Code Amendments for Disability Rights and Legal Protection - Nugroho, Harry; Utari, Indah Sri; Irawaty, Irawaty; Nugroho, Satrio Sakti; Ezzerouali, Souad; Sanni, Tajudeen (Indonesian Journal of Advocacy and Legal Services, 2025)
The Constitutional Court of Indonesia’s Decision Number 93/PUU-XX/2022 marks a pivotal moment in disability rights by ruling that the terms “imbecile,” “mentally ill,” and “dark-eyed,” along with the word “must” in Article 433 of the Civil Code, are inconsistent with the 1945 Constitution. The Court replaced these derogatory terms with “persons with mental and/or intellectual disabilities” and revised “must” to “can,” signaling a shift toward a more rights-based approach. However, this legal amendment raises critical questions: Does it effectively balance guardianship proceedings with the rights and autonomy of persons with disabilities? And who will advocate for their protection and inclusion in the legal system? This study analyzes the decision’s implications, particularly its impact on the legal mechanisms available to individuals with mental and intellectual disabilities. Using a qualitative approach and a statutory analysis of the Civil Code, Law No. 8 of 2016 on Disability, Law No. 19 of 2011 on the Protection and Rights of Persons with Disabilities, and the Constitutional Court ruling, this research evaluates the extent to which the amendments align with international human rights standards, such as the UN Convention on the Rights of Persons with Disabilities (CRPD). By placing Indonesia’s legal reforms in the broader international debate on disability rights, this study highlights the urgency of stronger advocacy and legal safeguards to prevent continued marginalization. The findings contribute to discussions on legal capacity, guardianship, and human dignity, offering insights for policymakers, legal practitioners, and human rights advocates seeking to advance disability rights worldwide.